2012
DOI: 10.1515/ans-2012-0311
|View full text |Cite
|
Sign up to set email alerts
|

On the Orbital Stability of Standing-Wave Solutions to a Coupled Non-Linear Klein-Gordon Equation

Abstract: We show the existence of standing-wave solutions to a coupled non-linear Klein-Gordon equation. Our solutions are obtained as minimizers of the energy under a two-charges constraint. We prove that the ground state is stable and that standing-waves are orbitally stable under a non-degeneracy assumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…In [23] the precompactness of minimizing sequences is obtained assuming N = 1. To exclude the dichotomy the authors crucially applied [1, Lemma 2.10] which depends in turn on original ideas introduced in [5], see also [12]. In [1, Lemma 2.10] it is shown that the H 1 (R) norm of some functions are strictly decreasing when the masses of the functions are symmetrically rearranged.…”
Section: Introductionmentioning
confidence: 99%
“…In [23] the precompactness of minimizing sequences is obtained assuming N = 1. To exclude the dichotomy the authors crucially applied [1, Lemma 2.10] which depends in turn on original ideas introduced in [5], see also [12]. In [1, Lemma 2.10] it is shown that the H 1 (R) norm of some functions are strictly decreasing when the masses of the functions are symmetrically rearranged.…”
Section: Introductionmentioning
confidence: 99%
“…and the assumption (1.2) made in [8]. In Proposition 3.5 we prove that the coupling term of functions satisfying (1.2) must be non-positive and monotonically non-increasing on each component; we can also show that there are non-linearities satisfying our assumptions (A 0 )-(A 4 ) with a sign-changing coupling term.…”
Section: Introductionmentioning
confidence: 59%
“…We conclude by showing that our assumptions are too general to allow an approach based on the symmetric rearrangement and inequality (1.2), as it has been done in [8] or [2]. We de ne 4 ( , ) := − | | + | | + | | + | | , > 0, where 2 < 2 < 2 < < 2 * and = 2.…”
Section: Proposition 32 There Holds Inf( ) = 2 = Inf(λ)mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, most works treat the problem in which the parameters such as σ 1 , σ 2 , c are being fixed. There are very few papers which deal with the existence problem of prescribed L 2 -norm solutions, for instance, see [1,2,4,17,27] for the results on prescribed L 2 -norm solutions to two-component coupled systems. Up to our knowledge, [8,20] are the only available works which obtain prescribed L 2 -norm solutions for coupled nonlinear systems with three or more equations.…”
Section: Introductionmentioning
confidence: 99%